Ancient Chinese fables for teaching Chinese as a third language in UiTM / Yap Soh Leay, Wong Hoong Cheong and Goh Ying Soon - Cheong, Wong Hoong; Soon, Goh Ying; Leay, Yap Soh (2021)
Ancient Chinese fables are stories with allegoric or educational significance in ancient China. The length of this literary genre is short, but the language is very refined. The content of ancient Chinese fables is simple but always brings out profound wisdom from the stories. The existing research of ancient Chinese fables on teaching Chinese as a foreign language is quite lacking. In fact, the application of ancient Chinese fables in teaching Chinese as a foreign language has great practical values. Story pedagogy and gamification teaching activities can increase non-Chinese learners' interest, motivation and learning effectiveness. The effective teaching method such as gamification teaching activities using card games, slides and learning sheet (CSLS), visual image and video, word puzzles, word guessing games and theatrical games can boost the learners' concentration, deepen their memory, improve their listening, speaking, reading and writing skills. Furthermore, non-Chinese learner will get closer to the extensiveness and profoundness of traditional Chinese culture by through learning ancient Chinese fables. This study will refer to the course syllabus of teaching Chinese as a third language at UiTM as an example to explore the application and effectiveness of ancient Chinese fables in teaching Chinese as a third language in UiTM. The limitations of this teaching method and solutions will also be discussed in this article. The research significance of this article is by giving some suggestions in teaching the ancient Chinese fables. Looking forward to these suggestions can serve to induce contributions in the teaching Chinese as third language in UiTM